2011
DOI: 10.5755/j01.ms.17.4.779
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Elastane Fibre on the Woven Fabric Structural Mobility

Abstract: The woven fabrics structural mobility has some influence on the garment design and pattern construction. Deformation peculiarities during six textile fabrics extension were analysed in this work. Four of the tested fabrics had the elastane filaments in their structure. The method of parallelepiped shaped specimen uniaxial extension till fixed strain was used. The experiment was carrying out using a "Tinius Olsen HT10" tension machine. The specimens' deformation exceeds 14 %. The parallelepiped shape of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…used strain-stress curves, numerical and graphical results to investigate woven fabrics structure mobility. They found that deformation peculiarities of the woven fabrics depend on their structural characteristics: density, thickness, wave and presence of elastane filaments [27].…”
Section: Introductionmentioning
confidence: 99%
“…used strain-stress curves, numerical and graphical results to investigate woven fabrics structure mobility. They found that deformation peculiarities of the woven fabrics depend on their structural characteristics: density, thickness, wave and presence of elastane filaments [27].…”
Section: Introductionmentioning
confidence: 99%
“…In another study on the effect of elastane draft ratio and yarn twist coefficient, it was found that the bagging fatigue of woven fabrics is reduced by using higher elastane draft and lower twist coefficient [19]. The effect of elastane fiber on the structural mobility of the woven fabrics has also been studied, and it is reported that the fabric structural mobility may be guaranteed by using elastane fibers in both fabric directions [20].…”
Section: Introductionmentioning
confidence: 99%
“…Tsai et al (2002) evaluated the influence of woven fabrics' stretch properties on garment design and pattern construction. Sacevičienė, Masteikaitė, Klevaitytė, and Audzevičiūtė (2011) showed that only elastane fibers in both warp and weft directions may guarantee the high structural mobility of the woven fabric. Hassan, El-Salmawy, and Almetwally (2010) investigated some performances of cotton/spandex-woven fabrics containing spandex such as elongation, shrinkage, and extension as well as the effect of spandex ratio on these performances.…”
Section: Introductionmentioning
confidence: 98%